Effect Of Packaging Films On Cell Wall Hydrolyzing Enzymes In Relation To Shelf Life Enhancement Of Tomatoes Stored Under Ambient Conditions (Applied Biological Research, 2017)
The effect of packaging films on post-harvest life span of tomato in relation to their effect on the activities of potential cell wall hydrolyzing enzymes  were investigated. Tomato cv. ‘Punjab Upma’ and ‘Punjab Ratta’ picked  at pink stage were placed in open trays, high density polyethylene (HDPE)-,  low density polyethylene (LDPE)- and polypropylene (PP)-bags and stored  under ambient conditions till their edible state. Irrespective of the variety,  there was enhancement in the activities of cell wall hydrolyzing enzymes  i.e. polygalacturonase, pectin methylesterase, cellulase and β-galactosidase. Further, there was decrease in firmness with increase in storage period. However, less changes were noticed in tomatoes packaged in polythene bags in comparison to those kept in open trays. Tomato cv. ‘Punjab Ratta’ displayed slow increase in the activities of cell wall hydrolases and less decrease in firmness as compared to cv. ‘Punjab Upma’. In both the varieties, LDPE packaging showed slowest changes in enzymatic activities and firmness and were efficient in enhancing the shelf life of tomatoes.
Keywords: Cell wall hydrolyzing enzymes; firmness; packaging; post harvest; shelf life; tomatoes